Intonation Trends in News Broadcast - Oleinik, Helen (Respectus Philologicus, 2006)
The suggested article is concerned with mass media communication. The prosodic level of the Russian mass media speech is exposed to the substantial influence of the English intonation.The aim of the research is to compare the prosodic features of the English and the Russian mass media broadcast. The findings of the experiment enable us to state that l) the variety of mass media communication undergoes the process of unification and 2) the definite type of English intonation loans is found in the Russian media discourse.The research singled out 1) the intonation parameters that provide the Russian media speech with English-like sounding and 2) the genres of broadcasting where the referred phenomena occur.
Keywords: mass media communication; mass media discourse; modem tendencies in the mass media discourse; intonation loans; media intonation innovations; English like sounding of the Russian mass media texts